Appropriation strategies and open innovation in SMEs. (August 2017) - Freel, Mark; Robson, Paul J
Drawing upon data from the fifth UK Innovation Survey, this article sheds light on how management choices on the nature of appropriation relate to management choices on the degree of openness within small and medium-sized enterprises (SMEs). To this end, our findings indicate a threshold effect of both informal and formal appropriation mechanisms on the likelihood of engaging in both coupled and inbound open innovation. That is, an emphasis on appropriation appears to be important in shifting firms from a closed to an open strategy. There is, however, little evidence that either approach to appropriation increases the extent of open innovation. In this, only informal intellectual property (IP) protection mechanisms associate with an increasing extent of inbound open innovation.